A Pedagogical Strategy for Integrated Education of Spanish in the 4th to 6th Grades of the General Basic Education - Barboza Navarro, Mireya (2011)
Language teaching has become a priority in the Costa Rican educational system, considering it as a tool for communication and development of thought. Without language, there is no access to other curriculum disciplinary knowledge. A successful experience conducted some years ago, with students from 4th to 6th grade, was the basis for the design and implementation of a professional development activity addressed to promoting an integration strategy previously adjusted according to the Ministry’s requirements and the existing national regulations. This study is developed in the framework of a qualitative paradigm including research-action and systematization. A purposive sample was selected based on a suitability factor, through which individuals are informed about the strategy, and then the strategy is applied to a group of students from urban-marginal areas. The techniques used include literature review, analysis of curriculum and Ministry’s regulations, application of an in-depth interview, discussions from the course’s participant in a portfolio, and discussions from students to whom the strategy was applied. We analyzed the considerations of teachers and students, as well as the theoretical and regulatory information by triangulation. The study’s conclusion is the necessity of a communicative approach in language teaching and our recommendation is to implement the strategy developed in the Costa Rican classrooms as provided in this paper.